Educational Supervision under the challenges in the Digital Era - Nisae, Supakon; Haung-keawphrai, Surasit; Boonsong, Kanchana; Petsom, Nipa (Journal of MCU Phetchaburi Review, 2025)
The academic article on "Educational Supervision Guidelines under Challenges in the Digital Age" aims to present the essential content related to educational supervision guidelines under challenges in the digital age, which is the focus of current studies. To be consistent with the various changes in the world today, this article presents the essential content, including the meaning of educational supervision, basic concepts of educational supervision, the educational supervision process, the application of digital technology in educational supervision, challenges encountered in educational supervision in the digital age, and differences between traditional educational supervision and educational supervision in the digital age, by reviewing, analyzing, and synthesizing documents, academic articles, and various related sources. The study found that amidst various changes, especially changes in current digital technology, educational supervision poses several challenges for supervisors and supervisees, namely rapid changes in technology, development of teachers’ digital skills, management of learner diversity, monitoring and evaluating learning outcomes, management of digital resources, and issues of security and privacy of educational supervision data. Therefore, supervisors and supervisees must apply digital technology to educational supervision in various aspects, such as using digital technology to help collect and analyze data, evaluate teaching results, provide continuous suggestions, train and develop personnel, create learning networks, and adapt to the times. This is an important tool for developing the quality of education and the work of teachers very well.